2015
DOI: 10.1016/j.jhtm.2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the travel patterns, preferences and recommendations of Chinese university students living in Australia

Abstract: a b s t r a c tChina is an important and growing market for the Australian tourism industry, yet our understanding of what Chinese independent tourists seek in the way of experiences is limited. Studies in Europe, USA and Australia show that Chinese international students tend to travel extensively while studying overseas, and consequently are able to provide insights into the needs, preferences and perceptions of the emerging Chinese independent market. Using Chinese tertiary students studying in Australia as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(56 citation statements)
references
References 34 publications
(47 reference statements)
3
51
0
1
Order By: Relevance
“…Such findings are consistent with Chadee and Cutler (1996) and Michael et al (2004). The findings also disagree with the more recent studies of Hughes et al (2015) indicating that holiday packages with travel Anatolia, 28(3), 394-403. doi:10.1080Anatolia, 28(3), 394-403. doi:10. /13032917.2017 13 agents are well sought by MCIS in Australia.…”
Section: Exploring Information Source Preferencessupporting
confidence: 56%
See 3 more Smart Citations
“…Such findings are consistent with Chadee and Cutler (1996) and Michael et al (2004). The findings also disagree with the more recent studies of Hughes et al (2015) indicating that holiday packages with travel Anatolia, 28(3), 394-403. doi:10.1080Anatolia, 28(3), 394-403. doi:10. /13032917.2017 13 agents are well sought by MCIS in Australia.…”
Section: Exploring Information Source Preferencessupporting
confidence: 56%
“…Numerous respondents believe that using a combination of both recommendations from family and friends as well as the Internet was most reliable. Although Some findings are thus similar to Hughes et al (2015) arguing that MCIS tend to rely on the Internet and word-of mouth advertising whereas Xu et al (2009) suggest that they are less reliant on commercial advertisement and more on recommendations from friends and family. None of respondents planned their holiday based on brochures obtained from visitor centres and travel agents.…”
Section: Exploring Information Source Preferencesmentioning
confidence: 53%
See 2 more Smart Citations
“…Issues around visitation are compounded by the finding that Indigenous tourism is not a ‘primary travel motivator’ for international visitors but is rather a ‘minor component of an overall cultural or natural experience and is generally perceived as less attractive than other activities’ (Ryan and Huyton, 2000, 2002; Whitford and Ruhanen, 2010, p. 26). Research has also demonstrated that Chinese tourists are largely uninterested in Indigenous tourism and do not express much intention to participate in such experiences (Whitford et al , 2001; Whitford and Ruhanen, 2010; Ruhanen et al , 2014, 2015; Hughes et al , 2015).…”
Section: Introductionmentioning
confidence: 99%